Metal Levels in Blood of Three Species of Shorebirds during Stopover on Delaware Bay Reflect Levels in Their Food, Horseshoe Crab Eggs - Joanna Burger; Nellie Tsipoura; Michael Gochfeld (Toxics, 2017)
Understanding the relationship between metal level in predators and their prey is an important issue, and is usually difficult to determine because animals eat a variety of organisms. However, shorebirds that stop over during spring migration along Delaware Bay (New Jersey) stay for only 2–3 weeks, and eat mainly horseshoe crab (Limulus polyphemus) eggs. In this paper, we examine the relationship between metal levels in horseshoe crab eggs, and blood and feather levels of metals in red knot (Calidris canutus rufa; n = 30), sanderling (Calidris alba; n = 20) and semipalmated sandpiper (Calidris pusilla; n = 38) from Delaware Bay. There is a rich literature on metal levels in feathers. For all three species, the levels of arsenic, cadmium, chromium, lead and mercury in blood were highly correlated with the levels of metals in the eggs of horseshoe crab (17 pooled samples). This indicates that the levels in the blood of these shorebirds quickly reflect levels in their prey (horseshoe crab eggs), while metals in the feathers were not correlated with the levels in eggs. Semipalmated sandpipers had the lowest levels of arsenic in blood and the highest levels of arsenic in feathers, compared to the other species. At Delaware Bay, semipalmated sandpipers have a diet higher in marsh invertebrates than the other species, which may account for the differences. The levels of cadmium and chromium in blood were significantly higher in knots than other species; knots only ate horseshoe crab eggs. For all of the metals except arsenic, the ratio of levels in blood/feathers was similar among species. For arsenic, the ratio of levels in blood/feathers were significantly lower in semipalmated sandpipers than in the other species, by an order of magnitude.